A faith-based environmental approach for people and the planet: Some inter-religious perspectives on our Earth-embeddedness - Puglisi, Antonino (HTS teologiese studies, 2022)
For most people on our planet, spiritual values are vital in driving communitarian behaviour. It is becoming increasingly clear that a lasting and effective social commitment must consider cultural, sociological and religious dimensions. In particular, the current environmental crisis has demonstrated how effectively religious communities have mobilised to respond to climate change. With their emphasis on wisdom, social cohesion and interrelationships, religions can be a strategic player in ensuring effective integral human development. The ecological crisis is not just an ethical dilemma but an ontological and theological matter that demands both a new way of thinking and a new way of being. Think differently and act differently! The United Nations (UN) and many governments are increasingly recognising the vital contribution of religious leaders and organisations in political processes, such as the 2030 Agenda for Sustainable Development, hypostasised in the Faith Plans for People and Planet programme, representing the most prominent and boldest environmental initiative to date by the global faith community.Contribution: Today we realise that a combination of science and spirituality can engage and empower an array of stakeholders from different cultural and religious backgrounds. This article addresses the question of an integrated ecology by selecting appropriate and recent literature from mainstream religions and the subsequent interpretation and application.